The evolving spectrum of interstitial lung disease in myositis—Management pearls - Takahisa Gono (Indian Journal of Rheumatology)
Idiopathic inflammatory myopathies (IIMs) are characterized by muscle inflammation caused by exacerbated autoimmunity reactions. Patients with IIMs also have extramuscular lesions, such as skin rash, arthritis, interstitial lung disease (ILD), and cardiomyopathy. ILD is one of the leading causes of mortality in patients with IIMs. Thus, physicians need to manage patients with IIM-associated ILD (myositis-ILD) appropriately to prevent the development and progression of ILD. Predictive factors for morality should be considered at the time of making decisions on therapeutic strategies for myositis-ILD. There have been numerous prognostic factors associated with mortality or pulmonary dysfunction. According to the latest research, which contains the large database analysis enrolling 499 incident cases of myositis-ILD with the comprehensive measurement of myositis-specific autoantibodies (MSAs), the presence of anti-melanoma differentiation-associated gene 5 antibody, age ≥60 years, C-reactive protein ≥1 mg/dL, and pulse saturation oxygen <95% have been identified as independent risk factors for mortality. We should also consider the severity of ILD, such as lower values of vital capacity and extensive ILD, and disease behavior to. The clinical characteristics of myositis-ILD are highly diverse. Thus, the categorization of homogenous groups by MSAs and prognostic factors is required to offer appropriate therapeutic regimens to individual patients with myositis-ILD. This effort will contribute to improve the daily quality of life as well as the survival rate in patients with myositis-ILD.